Aristophanes in Comic Books: Adaptation as Metabase - Asimakoulas, Dimitris (Meta, 2016)
Translation studies researchers have for a long time critically engaged with the idea of translation being a mode of creative rewriting across media and cultural or temporal divides. Adaptation studies experts use a similar premise to study products, processes and reception of adaptations for specific locales. This article combines such perspectives in order to shed light on an under-researched area of comic adaptation: this is the metabase, or transfer, of Aristophanic comedies to the comic book format in Greek and their subsequent translation into English for an e-book edition (Metaichmio Publications 2012). The paper suggests a model for the close reading of creative transfer based on Lefèvre’s (2011; 2012) typology of formal properties of comics and Attardo’s (2002) General Theory of Verbal Humour. As is shown, visual rhythm and text-image relations create a rich environment for anachronism, parody, comic characterisation and ideological comments, all of which serve a condensed plot. The English translation rewrites cultural/ideological references, amplifies obscenity and emphasizes narrator visibility, always taking into consideration the mise en scène.